Odpowiedź :
a)2⁻⁵/3⁻¹= 1/2⁵ / 1/3 = 1/32 *3 = 3/32
b)2⁻¹+6⁻¹= ½+⅙= 4/6=2/3
c)2⁻²+3⁻²=1/2² + 1/3² = 1/4 +1/9 = 9/36 + 4/36 = 13/36
d)2⁻⁵-4⁻² 1/32 - 1/4² = 1/32 - 1/16=1/32 - 2/32=-1/32
e)((jedna siodma)⁻²+1)⁻²=((1/ 1/7²) +1)⁻²=(1*7²+1)⁻²=50⁻²=1/50²=1/2500
f)((½)⁻²-1)⁻³ =(4-1)⁻³=3⁻³=1/3³=1/27
b)2⁻¹+6⁻¹= ½+⅙= 4/6=2/3
c)2⁻²+3⁻²=1/2² + 1/3² = 1/4 +1/9 = 9/36 + 4/36 = 13/36
d)2⁻⁵-4⁻² 1/32 - 1/4² = 1/32 - 1/16=1/32 - 2/32=-1/32
e)((jedna siodma)⁻²+1)⁻²=((1/ 1/7²) +1)⁻²=(1*7²+1)⁻²=50⁻²=1/50²=1/2500
f)((½)⁻²-1)⁻³ =(4-1)⁻³=3⁻³=1/3³=1/27
a)2⁻⁵/3⁻¹ = (1/2)^5 / 1/3 = 1/32 *3 = 3/32
b)2⁻¹+6⁻¹ = 1/2 + 1/6 = 6/12+2/12 = 8/12 = 4/6 = 2/3
c)2⁻²+3⁻² = (1/2)^2+(1/3)^2 = 1/4+1/9 = 9/36+4/36 = 13/36
d)2⁻⁵-4⁻² = (1/2)^5 - (1/4)^2 = 1/32 - 2/32 = -1/32
e)((1/7)⁻²+1)⁻² = (7^2+1)⁻² = (1/50)^2 = 1/2500
f)((½)⁻²-1)⁻³ = (4-1)^-3 = 1/3^3 = 1/27
b)2⁻¹+6⁻¹ = 1/2 + 1/6 = 6/12+2/12 = 8/12 = 4/6 = 2/3
c)2⁻²+3⁻² = (1/2)^2+(1/3)^2 = 1/4+1/9 = 9/36+4/36 = 13/36
d)2⁻⁵-4⁻² = (1/2)^5 - (1/4)^2 = 1/32 - 2/32 = -1/32
e)((1/7)⁻²+1)⁻² = (7^2+1)⁻² = (1/50)^2 = 1/2500
f)((½)⁻²-1)⁻³ = (4-1)^-3 = 1/3^3 = 1/27
a)2⁻⁵/3⁻¹=(1/2)^5/1/3 =1/32*3=3/32
b)2⁻¹+6⁻ =1/2 + 1/6 =6/12+2/12 =8/12=4/6=2/3
c)2⁻²+3⁻² = (1/2)^2+(1/3)^2 = 1/4+1/9 = 9/36+4/36 =13/36
d)2⁻⁵-4⁻² = (1/2)^5 - (1/4)^2 = 1/32 - 2/32 =(-1/32)
e)((1/7)⁻²+1)⁻² = (7^2+1)⁻² = (1/50)^2 = 1/2500
f)((½)⁻²-1)⁻³ = (4-1)^-3 = 1/3^3 = 1/27
b)2⁻¹+6⁻ =1/2 + 1/6 =6/12+2/12 =8/12=4/6=2/3
c)2⁻²+3⁻² = (1/2)^2+(1/3)^2 = 1/4+1/9 = 9/36+4/36 =13/36
d)2⁻⁵-4⁻² = (1/2)^5 - (1/4)^2 = 1/32 - 2/32 =(-1/32)
e)((1/7)⁻²+1)⁻² = (7^2+1)⁻² = (1/50)^2 = 1/2500
f)((½)⁻²-1)⁻³ = (4-1)^-3 = 1/3^3 = 1/27